Altered PLP1 splicing causes hypomyelination of early myelinating structures. Issue 6 (1st May 2015) - Kevelam, Sietske H.; Taube, Jennifer R.; van Spaendonk, Rosalina M. L.; Bertini, Enrico; Sperle, Karen; Tarnopolsky, Mark; Tonduti, Davide; Valente, Enza Maria; Travaglini, Lorena; Sistermans, Erik A.; Bernard, Geneviève; Catsman‐Berrevoets, Coriene E.; et al.
Abstract Objective The objective of this study was to investigate the genetic etiology of the X‐linked disorder "Hypomyelination of Early Myelinating Structures" (HEMS). Methods We included 16 patients from 10 families diagnosed with HEMS by brain MRI criteria. Exome sequencing was used to search for causal mutations. In silico analysis of effects of the mutations on splicing and RNA folding was performed. In vitro gene splicing was examined in RNA from patients' fibroblasts and an immortalized immature oligodendrocyte cell line after transfection with mutant minigene splicing constructs. Results All patients had unusual hemizygous mutations of PLP1 located in exon 3B (one deletion, one missense and two silent), which is spliced out in isoform DM20, or in intron 3 (five mutations). The deletion led to truncation of PLP1, but not DM20. Four mutations were predicted to affect PLP1/DM20 alternative splicing by creating exonic splicing silencer motifs or new splice donor sites or by affecting the local RNA structure of the PLP1 splice donor site. Four deep intronic mutations were predicted to destabilize a long‐distance interaction structure in the secondary PLP1 RNA fragment involved in regulating PLP1/DM20 alternative splicing. Splicing studies in fibroblasts and transfected cells confirmed a decreased PLP1/DM20 ratio. Interpretation Brain structures that normally myelinate early are poorly myelinated in HEMS, while they are the best myelinated structures in Pelizaeus–Merzbacher disease, also caused by PLP1 alterations. Our data extend the phenotypic spectrum of PLP1‐related disorders indicating that normal PLP1/DM20 alternative splicing is essential for early myelination and support the need to include intron 3 in diagnostic sequencing.